ANALISIS KESENJANGAN IMPLEMENTASI STANDAR KESELAMATAN KERJA PENGELASAN SD-36-3020 DI PT X BERDASARKAN STANDARD NFPA 51 B : 2014 - Riki Wahyu Aditias; Suroto Suroto; Hanifa Maher Denny (Jurnal Kesehatan Masyarakat (Undip), 2018)
Welding safety standard is a program to ensure the safe work procedures in welding, cutting, and other hot work. Hot work duties are widely performed at PT. X. The purpose of this study was to analyze the gap between safety welding standards: SD-36-3020 and the NFPA 51 B: 2014. The type of this research was a qualitative with in-depth interview and observation to collect data.  The subject of this research was 6 informants. The results showed that there were 37 gaps out of 70 points between safety welding standards: SD-36-3020 and the NFPA 51 B: 2014. Moreover, 45 out of 50 observation points of welding safety standard: SD-36-3020 had been fulfilled. There were differences in perceptions related to welding safety standards, safety sign tags were not available, welding cable was not tight, and water hose for emergency conditions and welding curtain were not available. Several 38 point had been implemented and met the standard of NFPA 51 B: 2014. Recommendation there some aspects need to be improve pertaining to the welding and hot work duties the NFPA 51 B: 2014.